Application of an Amyloid Beta Oligomer Standard in the sFIDA Assay - Kühbach, Katja; Hülsemann, Maren; Herrmann, Yvonne; Kravchenko, Kateryna; Kulawik, Andreas; Linnartz, Christina; Peters, Luriano; Wang, Kun; Willbold, Johannes; Willbold, Dieter; Bannach, Oliver (Frontiers in Neuroscience, 2016)
Still, there is need for significant improvements in reliable and accurate diagnosis for Alzheimer’s disease (AD) at early stages. It is widely accepted that changes in the concentration and conformation of amyloid-β (Aβ) appear several years before the onset of first symptoms of cognitive impairment in AD patients. Because Aβ oligomers are possibly the major toxic species in AD, they are a promising biomarker candidate for the early diagnosis of the disease. To date, a variety of oligomer-specific assays have been developed, many of them ELISAs. Here, we demonstrate the sFIDA assay, a technology highly specific for Aβ oligomers developed towards single particle sensitivity. By spiking stabilized Aβ oligomers to buffer and to body fluids from control donors, we show that the sFIDA readout correlates with the applied concentration of stabilized oligomers diluted in buffer, cerebrospinal fluid (CSF), and blood plasma over several orders of magnitude. The lower limit of detection was calculated to be 22 fM of stabilized oligomers diluted in PBS, 18 fM in CSF and 14 fM in blood plasma.